ASIX: Single-photon, energy resolved X-ray imaging with 50 μm hexagonal hybrid pixel - Minuti, Massimo; Baldini, Luca; Beccherle, Roberto; Bellazzini, Ronaldo; Bisht, Ashish; Boscardin, Maurizio; Brez, Alessandro; Bruschi, Paolo; Ceccanti, Marco; Vignali, Matteo Centis; Frontini, Luca; Gaioni, Luigi; et al. (Frontiers in Sensors, 2025)
The Analog Spectral Imager for X-rays is a technology demonstrator of a small-pixel Hybrid Pixel Detector (HPD) designed for applications such as X-ray diffraction, synchrotron-based material science, and soft X-ray astrophysics requiring energy-resolved imaging. The ASIX architecture aims at mitigating the adverse effects of charge sharing, typical of small-pixel devices. In contrast to other frame-based photon counters or multi-threshold devices, ASIX employs, along with a 50 μm pixel, an ultra-low-noise (<30 e− ENC), fully analog, asynchronous, single-photon readout, targeting 10μm spatial resolution and 350 eV FWHM at 8 keV within the same exposure. In 2025, we began developing a small scale (∼5×5 mm2) HPD coupling a 300 μm-thick, n-on-p, edgeless silicon sensor with 50 μm pixels arranged in a hexagonal pattern to a newly designed 65-nm CMOS readout ASIC, featuring single-photon readout and on-chip analog to digital conversion, with a target rate capability of 108 ph/s/cm2. While the baseline for the ASIX R&D sensor is silicon for ≤20 keV operation, the design of the readout ASIC is compatible with High-Z materials sensors, such as cadmium-telluride or gallium-arsenide, for higher energies X-rays imaging, enabling potential extension to biomedical and preclinical research. This paper describes the ASIX imager architecture and reports on the development and testing of two Minimum Viable Products (MVPs), developed by coupling XPOL-III, a readily available 180-nm CMOS readout ASIC, to a 300 μm thick silicon sensor with 50 μm pixels and to a 750 μm thick CdTe sensor with 100 μm pixels, respectively. The MVPs achieved estimated energy resolution of 780eV FWHM at 17.5 keV (CdTe), and 620eV FWHM at 9.7 keV (silicon) and spatial resolution of 20μm (CdTe) and 7μm (silicon). These results confirm our preliminary models predicting the feasibility of simultaneous high energy and spatial resolution in such a small-pixel devices, thus securing the ASIX specifications. Finally, the paper highlights the technology gaps that ASIX would potentially fill in both terrestrial and space applications.